Effectiveness of coagulants in primary treatment of effluents from processing fruits - Alcarraz C, Mario (2010)
Industrial effluents without treatment or supervision by the authorities pollute the environment. Solving the problem does not go only by the control, supervision and penalties for companies that generate effluents, require its own investigation as well as develop specific treatments, accessible and affordable that can be adopted by each industry. The primary treatment is removal by physical or chemical means a substantial part of sedimentable or floating material, reducing an important fraction of the organic load, which represents a significant percentage of solid contaminants. Within the types of primary treatment quote coagulation and flocculation. The main objective was to evaluate the efficacy of two coagulants in reducing the pollution potential of effluents from the fruit processing plant. To make the primary treatment: were assayed two chemical substances, aluminum sulfate as inorganic coagulant and other organic, the Polycat CS-5460. The effectiveness was determined by turbidity assays, biochemical oxygen demand and total solids. We conclude that the best coagulant for the removal organic matter in effluents from the processing of fruit is the Polycat CS-5460 having achieved an important removal of turbidity (98.1%) and reduction of biochemical oxygen demand (96.58%) within allowable limits for discharge of industrial effluents, according peruvian law.